2001
DOI: 10.1071/ea00206
|View full text |Cite
|
Sign up to set email alerts
|

Ripening of climacteric fruits initiated at low ethylene levels

Abstract: Mature, unripe mango, peach, custard apple, kiwifruit and tomato were stored at 20˚C in air containing ethylene at <0.005, 0.01, 0.1 1.0 and 10 L/L. The time to ripen of all the climacteric fruits increased linearly with logarithmic decrease in ethylene concentration over the whole concentration range examined. Similar observations were also obtained with kiwifruit and custard apple held at 0 and 14˚C, respectively. However, the sensitivity of fruits to ethylene varied with banana and kiwifruit > custard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 12 publications
0
30
0
2
Order By: Relevance
“…Commercially, bananas are harvested at the green ripening stage and, after shipping to Italy, ripening is induced by gaseous ethylene, in order to start the climacteric phase, during which they will develop the characteristic aroma, taste and color. The minimal dose of exogenous ethylene capable of promoting ripening of the ‘Gros Michel’ banana is 0.1–1.0 µL L −1 and the concentration threshold necessary to initiate banana ripening is 0.1 µL L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Commercially, bananas are harvested at the green ripening stage and, after shipping to Italy, ripening is induced by gaseous ethylene, in order to start the climacteric phase, during which they will develop the characteristic aroma, taste and color. The minimal dose of exogenous ethylene capable of promoting ripening of the ‘Gros Michel’ banana is 0.1–1.0 µL L −1 and the concentration threshold necessary to initiate banana ripening is 0.1 µL L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene is known to regulate or coordinate fruit ripening and softening in climacteric fruit (Lelievre et al, 1997). Exposure to ethylene of either endogenous or external sources can reduce the postharvest life of climacteric and other fruit and vegetables by accelerating ripening or senescence processes (Reid, 1985), and recent studies have shown that ultra low levels of ethylene (5 nL·L -1 ) can influence the time to ripen of climacteric fruit (Wills et al, 2001). The induction of ethylene responses and attendant changes in gene expression can be effectively delayed or reduced by inhibitors of ethylene action including silver thiosulphate (STS), and the cyclic olefins 2-5 norbornadiene, diazocyclopentadiene, and 1-methylcyclopropene (1-MCP) Serek, 1997, 1999).…”
mentioning
confidence: 99%
“…This plant hormone plays a vital role in fruit ripening, with ripening in climacteric fruits and expression of ripening‐related genes associated with a sharp increase in ethylene secretion (Golding and others ; Alexander and Grierson ; Hoeberichts and others ). The onset of ripening in banana begins with the release of endogenous ethylene as the fruit reaches full maturity or by treatment with exogenous ethylene obtained commercially (Wills and others ). This process is initiated when ethylene binds to its receptors and triggers a signal transduction process that brings about fruit‐ripening (Fluhr and Mattoo ).…”
Section: Maturity Indices Harvesting and Postharvest Treatmentmentioning
confidence: 99%